Atossa’s Dream Yoking Music and Dance, Antiquity and Modernity in Maurice Emmanuel’s Salamine (1929) - Dorf, Samuel (Les Cahiers de la Société québécoise de recherche en musique)

(untitled) (Société québécoise de recherche en musique, 2012)
This essay explores the conflicting trends of tradition and modernism, unity and independence in Parisian musical and dance culture in the late 1920s through an analysis of Maurice Emmanuel’s (1863-1938) aesthetics of contemporary and ancient Greek music and dance. It begins by outlining and critiquing Emmanuel’s relevant scholarly contributions to ancient Greek dance history and music history before demonstrating how these tensions manifested in the 1929 production of Emmanuel’s opera Salamine based on Aeschylus’s The Persians. Exploring Emmanuel’s aesthetics of music and dance (ancient and modern) affords a unique opportunity to see how these creative media were theorized and practiced in the tumultuous years after the Ballets russes, while illustrating some of the conflicts between what Léandre Vaillat termed “the academic and the eurhythmic” in dance and music.